Obstructive sleep apnoea in children with craniofacial syndromes - Cielo, Christopher M. (Paediatr Respir Rev, 2014)
Obstructive sleep apnoea syndrome (OSAS) is common in children. Craniofacial anomalies such as cleft palate are among the most common congenital conditions. Children with a variety of craniofacial conditions, including cleft palate, micrognathia, craniosynostosis, and midface hypoplasia are at increased risk for OSAS. Available evidence, which is largely limited to surgical case series and retrospective studies, suggests that OSAS can be successfully managed in these children through both surgical and non-surgical techniques. Prospective studies using larger cohorts of patients and including polysomnograms are needed to better understand the risk factors for this patient population and the efficacy of treatment options for OSAS and their underlying conditions.